Congenital anosmia and emotion recognition: A case-control study. (June 2015) - Lemogne, Cédric; Smadja, Julien; Zerdazi, El-Hadi; Soudry, Yaël; Robin, Marion; Berthoz, Sylvie; Limosin, Frédéric; Consoli, Silla M.; Bonfils, Pierre
Abstract: Patients with anosmia are not able to detect volatile chemicals signaling the presence of infectious and non-infectious environmental hazards, which typically elicit disgust and fear, respectively. Social animals may compensate a loss of olfaction by taking advantage of signals of threat that are produced by their conspecifics. Among humans and other primates, body postures and facial expressions are powerful cues conveying emotional information, including fear and disgust. The aim of the present study was to examine whether humans with agenesis of the olfactory bulb, a rare disorder characterized by congenital anosmia, would be more accurate in recognizing facial expressions of fear and disgust. A total of 90 participants with no history of mental disorder or traumatic brain injury were recruited, including 17 patients with congenital anosmia (10 men, mean age±standard deviation: 36.5±14.8 years), 34 patients with acquired anosmia (18 men, mean age±standard deviation: 57.2±11.8 years) and 39 healthy subjects (22 men, mean age±standard deviation: 36.7±13.2 years). For each patient with congenital anosmia, the agenesis of the olfactory bulb was ascertained through magnetic resonance imaging. Emotion recognition abilities were examined with a dynamic paradigm in which a morphing technique allowed displaying emotional facial expressions increasing in intensity over time. Adjusting for age, education, depression and anxiety, patients with congenital anosmia required similar levels of intensity to correctly recognize fear and disgust than healthy subjects while they displayed decreased error rates for both fear (mean difference [95% confidence interval]=−28.3% [−46.3%, −10.2%], P =0.003) and disgust (mean difference [95% confidence interval]=−15.8% [−31.5%, −0.2%], P =0.048). Furthermore, among patients with acquired anosmia, there was a negative correlation between duration of anosmia and the rate of errors for fearful (Spearman's ρ =−0.531, P =0.001) or disgust (Spearman's ρ =−0.719, P <0.001) faces recognition. No significant difference was observed for the other primary emotions. Overall, these results suggest that patients with congenital anosmia and long-lasting acquired anosmia may compensate their inability to detect environmental hazards through olfaction by an increased ability to detect fear or disgust as facially expressed by others. Highlights: Olfactory bulb agenesis is a rare disorder characterized by congenital anosmia. Emotion recognition was examined with a morphing-based dynamic paradigm. Patients with congenital anosmia displayed less errors for fear and disgust. Patients with long-lasting acquired anosmia tended to display the same pattern. This may compensate their inability to detect environmental hazards with olfaction.